A Smart E-Learning System for Social Networking - M.R.M Veeramanickam; N. Radhika (International Journal of Electrical and Computer Engineering (IJECE), 2014)
With the development of Cloud Computing, the popularity of E learning, the increasing of social networking services, Smart Cloud E-Learning System with Social Networking has become a research topic. The characteristics of E learning Cloud and requirements of Social networking services in environments raise a challenge on building an Architecture and Implementation quite strong.  In this paper, we elaborate a Smart Cloud E-Learning System with Social Networking based on architecture level of social networking and E learning cloud system to support E learning interactions in worldwide environments.  A prototype of Cloud E-Learning System with Social Networking is developed on cloud, and several applications features are described based on the proposed architecture to demonstrate the effectiveness of the architecture.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5933